Examining Teachers’ and Students’ Perceptions of the Influence of Mobile Phones on the Quality of Research Data Collection. A Case Study of Second-Year EFL Master s’ Students at Mohammed- Cherif Messaadia University, Souk-Aharas. - Karima Senani (My University, 2026)
Abstract This study aims to examine teachers’ and second-year Master EFL students’ perceptions regarding the influence of mobile phones on the quality of research data collection at Mohamed Cherif Messaadia University, as well as to identify the advantages and challenges related to their use in academic research. The study employed a mixed-methods approach based on an exploratory design. An electronic questionnaire was administered to 40 Master EFL students, in addition to semi-structured interviews conducted with 7 English teachers. The findings revealed that mobile phones have become essential tools in academic research because they facilitate data collection, save time, improve communication with participants, and help organize research data more effectively. The results also showed that both teachers and students generally hold positive attitudes toward the use of mobile phones in research activities despite some challenges such as poor internet connection, technical problems, distractions during data collection, and concerns related to data reliability. The study concluded that mobile phones significantly contribute to improving the efficiency and accessibility of research data collection when used appropriately ------------------------------ الملخص تهدف هذه الدراسة إلى فحص تصورات المعلمين وطلاب السنة الثانية من برنامج ماجستير اللغة الإنجليزية كلغة أجنبية حول تأثير الهواتف المحمولة على جودة جمع البيانات البحثية في جامعة محمد شريف مسعدية، بالإضافة إلى تحديد مزايا وتحديات استخدامها في البحث الأكاديمي. استخدمت الدراسة منهجية بحثية مختلطة قائمة على تصميم استكشافي. وتم توزيع استبيان إلكتروني على 40 طالبًا من طلاب ماجستير اللغة الإنجليزية كلغة أجنبية، بالإضافة إلى إجراء مقابلات شبه منظمة مع 7 معلمين للغة الإنجليزية. وكشفت النتائج أن الهواتف المحمولة أصبحت أدوات أساسية في البحث الأكاديمي لما توفره من سهولة في جمع البيانات، وتوفير للوقت، وتحسين للتواصل مع المشاركين، والمساعدة في تنظيم البيانات البحثية بشكل أكثر فعالية. كما أظهرت النتائج أن كلاً من المعلمين والطلاب لديهم عمومًا مواقف إيجابية تجاه استخدام الهواتف المحمولة في الأنشطة البحثية على الرغم من بعض التحديات مثل ضعف الاتصال بالإنترنت، والمشاكل التقنية، وتشتت الانتباه أثناء جمع البيانات، والمخاوف المتعلقة بموثوقية البيانات. وخلصت الدراسة إلى أن الهواتف المحمولة تساهم بشكل كبير في تحسين كفاءة وسهولة الوصول إلى البيانات البحثية عند استخدامها بشكل مناسب --------------------------- Résumé Cette étude visait à examiner la perception des enseignants et des étudiants de deuxième année du master d'anglais langue étrangère (EFL) concernant l'impact des téléphones mobiles sur la qualité de la collecte de données de recherche à l'Université Mohamed Cherif Messaadia, ainsi qu'à identifier les avantages et les difficultés liés à leur utilisation dans la recherche universitaire. L'étude a adopté une approche de recherche mixte, basée sur un plan exploratoire. Un questionnaire en ligne a été diffusé auprès de 40 étudiants en EFL, et des entretiens semi-directifs ont été menés auprès de 7 enseignants d'anglais. Les résultats ont révélé que les téléphones mobiles sont devenus des outils essentiels dans la recherche universitaire grâce à leur facilité de collecte de données, le gain de temps qu'ils permettent, l'amélioration de la communication avec les participants et l'aide qu'ils apportent à une meilleure organisation des données. Les résultats ont également montré que les enseignants et les étudiants ont généralement une attitude positive envers l'utilisation des téléphones mobiles dans les activités de recherche, malgré certaines difficultés telles qu'une mauvaise connexion internet, des problèmes techniques, des distractions pendant la collecte de données et des préoccupations quant à la fiabilité des données. L'étude conclut que les téléphones mobiles contribuent significativement à améliorer l'efficacité et l'accessibilité des données de recherche lorsqu'ils sont utilisés de manière appropriée.
Keywords: Mobile Phones – Data Collection – Academic Research; الهواتف المحمولة - جمع البيانات - البحث الأكاديمي; Téléphones mobiles - Collecte de données - Recherche universitaire